The Contribution of Regional Tax to Regional Original Income of West Nusa Tenggara Province in 2018-2022 - Nisa Marlina; Muhamad Bai’ul Hak (Jurnal Ilmu Ekonomi, 2023)
This article analyzes the trend of regional tax contributions to Regional Original Income (PAD). The paper used descriptive quantitative approach by using secondary data. The secondary data used over period 2018-2022. The results show that the regional Income is a component of budgeting system in one province or district. In the regional income, regional tax plays an essential role as source of regional income. The higher regional tax, the higher regional original income of west Nusa Tenggara Province. The data explained that there is a slightly increase in both target and realization of regional tax. From 2018 to 2019, the realization always over to the target. On the other hand, from 2020 to 2022, the realization always under the target. Furthermore, the proportion of regional tax contributions to regional original income (PAD) is very high. Even though there are fluctuations from 2020 to 2022, the percentage is always above 50 percent of PAD.